The review of the monograph “Transport system: Models of development and forecast” (by Adolfas Baublys) - Paulauskas, Vytautas (Transport, 2003)
Major factors determining global economic development are the integration processes taking place now at all levels in Europe. They are aimed at the creation of the common European space.First Published Online: 19 Dec 2011